2011
DOI: 10.1017/s0022149x11000320
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Echinococcus granulosus in camels, cattle and sheep from the south-east of Iran indicates the presence of the G3 genotype

Abstract: Echinococcus granulosus, the aetiologic agent of cystic echinococcosis (CE), is one of the most important zoonotic helminthes worldwide. Isolates of the parasite show considerable genetic variation in different intermediate hosts. Several genotypes and species are described in different eco-epidemiological settings. This study investigated E. granulosus genotypes existing in livestock and humans from the province of Kerman, located in south-eastern Iran, using sequencing data of cox1 and nad1 mitochondrial gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 35 publications
(56 reference statements)
8
35
2
Order By: Relevance
“…Previous studies have indicated the presence of the G6 genotype in different hosts such as sheep, goats, cattle, camels, and humans in Iran. 28,29,32,40,56 However, the high prevalence of the G6 genotype in this study is not in accordance with previous human CE studies in Iran (Table 1), because most of these studies indicated the G1 genotype as the only genotype found in humans. However, the sample sizes used within some of the previously mentioned studies were very low.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have indicated the presence of the G6 genotype in different hosts such as sheep, goats, cattle, camels, and humans in Iran. 28,29,32,40,56 However, the high prevalence of the G6 genotype in this study is not in accordance with previous human CE studies in Iran (Table 1), because most of these studies indicated the G1 genotype as the only genotype found in humans. However, the sample sizes used within some of the previously mentioned studies were very low.…”
Section: Discussioncontrasting
confidence: 93%
“…Later, this genotype was reported by other researchers to be hosted in buffalo, sheep, cattle, and camels from different parts of the country. 29,35 In a recent study in (7) 6 (85.7) − − 1 (14.3) Total (125) 68 ( IREG1 32 G1 KF443137 IREG12 1 G3 KF443148 IREG2 14 G6 KF443138 IREG13 1 G3 KF443149 IREG3 8 G6 KF443139 IREG14 1 G2 KF443150 IREG4 4 G6 KF443140 IREG15 1 G1 KF443151 IREG5 4 G1 KF443141 IREG16 1 G1 KF443152 IREG6 3 G3 KF443142 IREG17 1 G1 KF443153 IREG7 2 G1 KF443143 IREG18 1 G1 KF443154 IREG8 2 G6 KF443144 IREG19 1 G1 KF443155 IREG9 2 G1 KF443145 IREG20 1 G1 KF443156 IREG10 2 G6 KF443146 IREG21-IREG41 21 G1 KF443157-KF443177 IREG11 1 G1 KF443147 IREG42-IREG62 21 G6 KF443178-KF443198 CE = cystic echinococcosis; CO1 = cytochrome c oxidase subunit I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to genotype hydatid cysts in human, sheep, goat, cattle, buffalo, and camel populations in Iran on the basis of mitochondrial (cox1 and nad1) and nucleus markers, using RAPD-PCR, PCR-RFLP and sequencing strategies (19,20,22,28,30,36,37). However, none of them could provide remarkable applications in mixed genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…could interact. These questions have subsequently been resolved with the advent of reliable, robust and reproducible molecular tools which have not only supported the early taxonomy, but also demonstrated the distinctness of transmission cycles and the potential for interaction, particularly with respect to zoonotic transmission [95,103,106]. Importantly, these molecular epidemiological studies have given confidence to the morphological characters used for species discrimination which now offer a simple, cost effective means of parasite identification in endemic foci where the application of molecular tools may not be practical or cost-effective [107,108].…”
Section: Echinococcus Giardia and Cryptosporidiummentioning
confidence: 99%